WRITTEN HISTORY OF VERBAL PREFIXATION IN THE OLD UKRAINIAN LITERARY LANGUAGE OF THE 14TH – 17TH CENTURIES - Kocherga, Halyna (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
The article investigates the structural and motivational aspect of verb prefixation recorded in the Old Ukrainian literary language of the 14th – 17th centuries. The linguistic marker of verb ellipsis is established, which implies the possibility of double motivation, which is based on a combination of morphological, onomasiological and semasiological approaches, taking into account the etymological segment of prefixes. The purpose of the article is to consider the internal structure of the prefixal verb subsystem of the Old Ukrainian language of the 14th – 17th centuries and to establish the motivational segment in derived derivatives, which forms the word-formation model of nomination. The word-forming model of structural-motivational and functional factors of the verb subsystem of the Old Ukrainian literary language of the 14th – 17th centuries, produced by the word-forming potential and means of its implementation, is revealed. The productivity of prefixal word-forming nominals is characterized by word-forming prefixal models that are structurally and semantically motivated by the onomasiological basis of the root verb. Historical word-formation studies show that in the language of written monuments of the 14th – 17th centuries there is a clear tendency to increase the role of prefixation in the verb segment, which naturally affects the activity of individual prefixes. Verb prefixes perform a species-recognition function, that is, they lead to a change in the type of basic verbs and modify the meaning of the state under various qualitative functions. In many groups of verbs, prefixes performed with additional meanings that differed from prepositional structures. The paradigmatic relationship of verb prefixes to the syntactic constructions in which they were segmented revealed the model of affixation as a semantic-word-forming process. The relationship of prefixes with some prepositions and their change in the meaning of the verb have an impact on the entire semantic structure of the sentence in which they are located, not only in content but also in form. Verbal prefixation as a method of word formation arose in the Proto-Slavic period, and the prefix systems of modern Slavic languages are its natural continuation.